2004
DOI: 10.1016/j.ccr.2004.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Lack of sustained regression of c-MYC-induced mammary adenocarcinomas following brief or prolonged MYC inactivation

Abstract: Recent studies of oncogene dependence in conditional transgenic mice have suggested the exciting possibility that transient or prolonged MYC inactivation may be sufficient for sustained reversal of the tumorigenic process. In contrast, we report here that following oncogene downregulation, the majority of c-MYC-induced mammary adenocarcinomas grow in the absence of MYC overexpression. In addition, residual neoplastic cells persist from virtually all tumors that do regress to a nonpalpable state and these resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
139
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 21 publications
12
139
0
Order By: Relevance
“…This finding suggests that as tumors increase in size, they acquire additional genetic alterations that allow them to become independent of the initiating oncogene, IGF-IR. Regression rates observed with the 500 mm 3 tumors in the MTB-IGF-IR transgenics were similar to those observed in mammary tumors induced by Wnt1 (Gunther et al, 2003) or constitutively active ErbB2 (Moody et al, 2002) but considerably higher than regression rates observed in c-Myc-induced mammary tumors (D'Cruz et al, 2001;Boxer et al, 2004). The effect of tumor size on regression rates was not explored in these other doxycycline inducible mammary tumor models.…”
Section: Discussionmentioning
confidence: 61%
“…This finding suggests that as tumors increase in size, they acquire additional genetic alterations that allow them to become independent of the initiating oncogene, IGF-IR. Regression rates observed with the 500 mm 3 tumors in the MTB-IGF-IR transgenics were similar to those observed in mammary tumors induced by Wnt1 (Gunther et al, 2003) or constitutively active ErbB2 (Moody et al, 2002) but considerably higher than regression rates observed in c-Myc-induced mammary tumors (D'Cruz et al, 2001;Boxer et al, 2004). The effect of tumor size on regression rates was not explored in these other doxycycline inducible mammary tumor models.…”
Section: Discussionmentioning
confidence: 61%
“…18 Similarly, mammary tumors arising as a result of conditional c-Myc expression, continue to grow in a c-Myc-independent manner following inactivation of the oncoprotein. 19 Although it is tempting to attribute such tumorigenic behavior to the observed chromosomal changes or to otherwise dominant mutator effects of c-Myc, it is just as likely that it resulted from a prolonged effect on c-Myc target gene expression. It could be argued that this represents another form of genomic instability, although mechanistically not akin to those which first spring to mind.…”
Section: The "Oncogene From Hell" Reduxmentioning
confidence: 99%
“…To date, this study represents the first and only identification of a specific gene product that mediates the protective effect of hormones. However, the development of several new and elegant conditional transgenic mouse models for c-myc, wnt, Brca-1 and cneu offer the promise of similar experiments (Deng 2002, Gunther et al 2002, Gunther et al 2003, Boxer et al 2004, Chodosh 2005. Additionally, the identification of new candidate genes by microarray studies suggests that numerous genes can be tested for their roles in the hormoneinduced protective state using transgenic mouse models.…”
Section: P53mentioning
confidence: 99%